Velocity field of image points in satellite imagery of planet’s surface - V. Ya. Gecha; M. Yu. Zhilenev; V. B. Fyodorov; D. A. Khrychev; Yu. I. Hudak; A. V. Shatina (Российский технологический журнал, 2020)
This paper derives a formula for calculating the velocity of arbitrary point in the field of view of the satellite camera in the process of orbital imagery of the planet's surface. The formula describes the velocity as a function of the point coordinates in the image fixation plane, the focal length of the imaging camera, the orbital parameters of the satellite, the angular velocity of the planet’s rotation, the coordinates of the satellite’s true anomaly in the orbit, the orientation angles of the imaging camera relative to the orbit, and the angular velocity of the camera. The paper also provides examples of the formula use for calculating the velocity field of image points for different sets of imagery parameters.The formula is derived under the assumption that the planet is a homogeneous absolutely solid body, shaped as a ball, and rotating at a constant angular velocity; as a result, the satellite moves in a Keplerian orbit, with the planet located at one of the orbit’s foci. Despite this idealization, the derived formula can be used in developing algorithms for remote sensing of the Earth, for building and optimizing the image blurring compensators, for solving the problem of blurred image recovery, and for a number of other problems related to satellite imagery preparation, execution, and processing the results.